The Impact and Efficacy of E-Counselling in an Open Distance Learning Environment:A Mixed Method Exploratory Study. Issue 2 (3rd April 2023) - Wells, Rossano
ABSTRACT: This paper reports on the findings of a study which sought to investigate the impact and efficacy of technology-based counseling offered by the University of South Africa (Unisa), an Open and Distance Learning (ODL) institution. The study focused specifically on student perceptions of the services they had received from professionals based in the Gauteng regional center, in the context of academic admissions and support, career indecision, financial and psychosocial challenges. A client satisfaction questionnaire was administered to 30 students. The theoretical framework for the study was Activity theory, which is a philosophical and cross-disciplinary framework for studying different forms of human practices as development processes, with both individual and social levels interlinked simultaneously. A mixed-method approach was adopted to explore participants' experiences and perceptions of e-counseling. Quantitative data was analyzed using the Statistical Package for Social Sciences (SPSS). Open-ended responses contained in the questionnaire, were subjected to qualitative analysis using the Atlas.ti program. Accessibility, convenience, and efficiency were highlighted as significant benefits of e-counseling. Results of the study suggest that while e-counseling should not be construed as a substitute for traditional, face-to-face counseling and psychotherapy, particularly in respect of more severe emotional and psychological challenges, it can be a useful adjunct to traditional modes of practice. The study also has important quality assurance implications for student counseling practice in Open and Distance Learning (ODL) institutions, particularly with respect to informing online ethical imperatives.